Understanding the Poverty Puzzle in Central Kalimantan: A Regional Economic Perspective - Wardhana, Ibnu (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2025)
This study aims to provide an empirical explanation of the factors influencing poverty in Central Kalimantan Province by adopting a regional economic perspective. The research employs a panel data regression method, which combines cross-sectional and time-series data, analyzed using EViews 9 software. The variables examined include population size, unemployment rate, human development index, and income distribution inequality, with poverty rate as the dependent variable. The findings reveal that population size has a positive and statistically significant effect on poverty in Central Kalimantan, indicating that an increase in population tends to exacerbate poverty levels. In contrast, unemployment is found to have a positive but statistically insignificant impact, suggesting that joblessness alone may not be a strong standalone predictor of poverty in the region. The human development index exhibits a negative and significant relationship with poverty, confirming that improvements in education, health, and living standards effectively reduce poverty levels. Interestingly, income inequality, as measured by the Gini index, shows a negative but insignificant influence on poverty, implying that disparities in income distribution do not strongly affect poverty rates in this context. Collectively, the four variables—population, unemployment, human development index, and income inequality—are found to significantly influence poverty when considered together. These results underscore the importance of integrated regional development strategies that target not only economic growth but also improvements in human capital and demographic management to combat poverty effectively in Central Kalimantan.